(untitled) - Clement, Ernest W. (Chicago, 1904)
This book, as its title indicates, is intended to portray Japan as it is rather than as it was. It is not by any means the purpose, however, to ignore the past, upon which the present is built, because such a course would be both foolish and futile
Keywords: Japan,Nhật Bản; Description and travel,Mô tả và du lịch